Delivered dose quantification in prostate radiotherapy using online 3D cine imaging and treatment log files on a combined 1.5T magnetic resonance imaging and linear accelerator system. (July 2020) - Kontaxis, Charis; de Muinck Keizer, Daan M.; Kerkmeijer, Linda G.W.; Willigenburg, Thomas; den Hartogh, Mariska D.; van der Voort van Zyp, Jochem R.N.; de Groot-van Breugel, Eline N.; Hes, Jochem; Raaymakers, Bas W.; Lagendijk, Jan J.W.; de Boer, Hans C.J.
Highlights: First delivered dose reconstruction based on six degrees of freedom motion from online 3D cine-MR imaging and treatment log files. For most fractions no significant target dose decrease observed. Few fractions with outlier motion due to bladder/rectal filling causing large dose deviations. Automated fast dose reconstruction crucial for future MRI-guided treatments. Abstract: Background and purpose: Monitoring the intrafraction motion and its impact on the planned dose distribution is of crucial importance in radiotherapy. In this work we quantify the delivered dose for the first prostate patients treated on a combined 1.5T Magnetic Resonance Imaging (MRI) and linear accelerator system in our clinic based on online 3D cine-MR and treatment log files. Materials and methods: A prostate intrafraction motion trace was obtained with a soft-tissue based rigid registration method with six degrees of freedom from 3D cine-MR dynamics with a temporal resolution of 8.5–16.9 s. For each fraction, all dynamics were also registered to the daily MR image used during the online treatment planning, enabling the mapping to this reference point. Moreover, each fraction's treatment log file was used to extract the timestamped machine parameters during delivery and assign it to the appropriate dynamic volume. These partial plans to dynamic volume combinations were calculated and summed to yield the delivered fraction dose. The planned and delivered dose distributions were compared among all patients for a total of 100 fractions. Results: The clinical target volume underwent on average a decrease of 2.2% ± 2.9% in terms of D99% coverage while bladder V62Gy was increased by 1.6% ± 2.3% and rectum V62Gy decreased by 0.2% ± 2.2%. Conclusions: The first MR-linac dose reconstruction results based on prostate tracking from intrafraction 3D cine-MR and treatment log files are presented. Such a pipeline is essential for online adaptation especially as we progress to MRI-guided extremely hypofractionated treatments.